Clinical profile of congenital diaphragmatic hernia and their short-term outcome in a tertiary care neonatal unit: A retrospective study - Molugan, M; Kamalarathnam, C N; Muthukumaran, J (Indian Journal of Child Health, 2017)
Background: Recent developments in the antenatal diagnosis, surgical techniques, and neonatal intensive care had widely increased survival rates in neonates with congenital diaphragmatic hernia (CDH) in the western world. In developing countries, however, high mortality in neonates with CDH still continues to be a challenge. Objective: The aim of this study is to study the clinical profile of neonates with CDH and to analyze the various factors affecting mortality. Materials and Methods: In this retrospective study, 148 babies with a diagnosis of diaphragmatic hernia admitted to a tertiary care neonatal unit in South India, from the year 2010 to 2015, were reviewed. Results: The total survival rate was 58.1%, and the operative survival rate was 85.1%. Prenatal diagnosis was made in only 7 cases, and of these, 5 (71.42%) survived. Higher mortality was associated with age at admission